The impacts of the Farmers Market and Local Food Promotion programs. Issue 5 (20th October 2017) - O'Hara, Jeffrey K.; Coleman, Carlos
Abstract: Farmers Market Promotion Program (FMPP) and Local Food Promotion Program grants are awarded by the US Department of Agriculture to bolster local food markets. We assess the impacts of these programs by analyzing responses to a national survey of farmers market administrators, undertaking two case studies of grant recipients, and reviewing previous literature. We find that there is a high association of FMPP recipient markets with greater organizational administrative capacity and improved market performance between 2013 and 2014. Our case studies reveal how grants can be effective when the projects have strong stakeholder support and collaborate with other community organizations. We also describe how some of the pilot projects supported by FMPP led to more targeted local food grant programs.